Model Pembelajaran dan Implementasi Pendidikan Multikultural Dalam Pendidikan Islam dan Nasional - Deni Sopiansyah; Mohamad Erihardiana (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2021)
Deni Sopiansyah1, M Erihardiana2. In the world of education, there are negative impacts caused by the development of multicultural education for Indonesia's young generation, ranging from radicalism, discrimination, the loss of local culture, brawls to criminal acts from social media and the real world resulting from a lack of understanding of multicultural education in the current era. Therefore, it is important to understand the importance of understanding multicultural education for the younger generation, because in the era of change, one of the competencies needed in the world of education is the ability of the younger generation to solve problems (problem solving). This research method uses qualitative methods with a library research approach. The result of this research is, by cultivating the right multicultural education, it will produce a young generation in an era that is creative, innovative, and a generation with character, integrity and upholding tolerance according to the national identity of the Indonesian nation. With this research, it is expected to be able to contribute knowledge about the importance of multicultural education in the process of Islamic and national education